BUDGETARY POLITICS IN STUNTING HANDLING IN JEMBER REGENCY: GOOD FINANCIAL GOVERNANCE AND HUMAN RIGHTS PERSPECTIVES - Briyan Nanda Ivansyach; Tumija (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Jember Regency came into the national spotlight for recording the highest stunting prevalence in East Java based on the 2022 SSGI data, at 34.9%. This phenomenon demands an aggressive fiscal policy response as a form of state obligation. This study aims to analyze the effectiveness of the Jember Regency Government's budgetary politics in handling stunting from the perspectives of Public Finance and Citizenship. This research employs a qualitative descriptive method with a library research approach. The results indicate that the Jember Regency Government allocated a specific cross-agency budget reaching IDR 341 Billion in the 2023 Fiscal Year. However, there is a significant data disparity between the central survey (SSGI) and local data (Weighing Month), which affects the precision of budget targeting. From a citizenship perspective, the magnitude of this budget is a manifestation of non-physical state defense to save the next generation, although challenges in data accountability remain a major obstacle in fully fulfilling citizens' right to health.